2016
DOI: 10.1123/ssj.2015-0149
|View full text |Cite
|
Sign up to set email alerts
|

Embodied Experiences of Empowerment Among Female Tackle Football Players

Abstract: The purpose of this study was to explore the embodied nature of empowerment among women who play tackle football. Data collection involved semistructured interviews with 15 female football players in Western Canada. Interviews were audio-recorded, transcribed verbatim and analyzed thematically. Three themes emerged from the data suggesting that playing football was empowering as women experienced: a) feelings of strength related to the physicality of the game; b) a sense of breaking boundaries as they particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…It is widely understood that sport environments are profoundly gendered (Jeanes et al, 2021), and thus participants were asked about their experiences training with other women and in mixed-gender environments to explore their feelings of safety in these different contexts. Previous studies have found that participation in sport fosters social connectedness among women, which has profound positive impacts, emphasizing the importance of dedicated women's spaces (Liechty et al, 2016). In line with this, several participants described their experiences of sport with other women as being characterized by camaraderie and forming strong friendships.…”
Section: Safe Sport Environments? Gendered Conflicts and Tensionssupporting
confidence: 56%
“…It is widely understood that sport environments are profoundly gendered (Jeanes et al, 2021), and thus participants were asked about their experiences training with other women and in mixed-gender environments to explore their feelings of safety in these different contexts. Previous studies have found that participation in sport fosters social connectedness among women, which has profound positive impacts, emphasizing the importance of dedicated women's spaces (Liechty et al, 2016). In line with this, several participants described their experiences of sport with other women as being characterized by camaraderie and forming strong friendships.…”
Section: Safe Sport Environments? Gendered Conflicts and Tensionssupporting
confidence: 56%
“…By moving the marginalized stories of these female athletes to 'the centre of interest and concern', the woman becomes the author of her own experiences (Fairchild 1994, 373;Cauldwell 2003;Thorpe, Toffoletti and Bruce 2017, 376), rather than having a male-human discourse imposed on her experience (Thompson 1994, 174). 1) The opportunity to participate in teams that produce 'family-like' relationships based in trust and interpersonal support (Liechty, Willfong and Sveinson 2016;Migliacco and Berg 2007;Paul and Blank 2015) 2) The opportunity to work with a diverse group of women who share a common cause, partly centred around the origin and sustainability of the team and the league (Liechty, Willfong and Sveinson 2016;Migliacco and Berg 2007;Pelak 2002;Wedgewood 2004;Willson et al 2017) 3) The opportunity to act aggressively and engage in physicality in ways that have traditionally been denied to women, and in ways that female participants Descriptions of football, ice hockey or boxing as female bodywork in the pursuit of a male athletic ideal; that is, descriptions in the existing male discourse, ignore the ways that the female player experiences these sports as sites of expansion of her individual freedom, choice and empowerment, and as sites for the enjoyment of her resistant physicality (Theberge 2003, 506;Mierzwinski, Velija and Malcolm 2014, 74-75;McCaughey 1998, 283). The understanding of physical participation in such sports is a gendered understanding, affected by a history of non-participation or submerged experience.…”
Section: Expressions Of Female Empowerment In 'Masculine Sport'mentioning
confidence: 99%
“…experienced as personally enjoyable and pleasurable (Channon and Phipps 2017; Liechty, Willfong and Sveinson 2016; Migliacco and Berg 2007; Paul and Blank 2015; Roth and Bastow 2004; Theberge 2003; Velija, Mierzwinski and Fortune 2013)4) The potential to develop a new style or discourse of play that emanates from the female experience(Pelak 2002;Theberge 2003) 5) The opportunity to build bodies that are capable of exhibiting physical qualities, such as strength and power, that have been traditionally associated with male bodies(Liechty, Willfong and Sveinson 2016; Migliacco and Berg 2007;Theberge 2003;Velija, Mierzwinski and Fortune 2013; Wedgewood 2004).4 …”
mentioning
confidence: 99%
“…The information strip that connects gendered discourse to situational behavior could create the frozen body through RBTs. Physicality and gendered discourse are emergent themes within research conducted by Liechty et al (2016) in their analysis of female embodiment with tackle football and Velija et al (2013) examining female martial arts practitioners. An empowered self-defense program is crucial for this research, and the type of martial art should be intentional within the lived experience.…”
Section: Embodiment and The Lived Bodymentioning
confidence: 99%